1981
DOI: 10.1073/pnas.78.1.124
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of cloned unintegrated avian sarcoma virus DNA: viral DNA contains direct and inverted repeats similar to those in transposable elements.

Abstract: We have determined the nucleotide sequence of portions oftwo circular avian sarcoma virus (ASV) DNA molecules cloned in a prokaryotic host-vector system. The region whose sequence was determined represents the circle junction site-i.e., the site at which the ends ofthe unintegrated linear DNA are fused to form circular DNA. The sequence from one cloned molecule, SRA-2, shows that the circle junction site is the center of a 330-base-pair (bp) tandem direct repeat, presumably representing the fusion ofthe long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(89 citation statements)
references
References 36 publications
(34 reference statements)
4
85
0
Order By: Relevance
“…In cells infected with the wild-type RSV, about half of the primary transcripts are spliced to generate env and v-src subgenomic mRNAs, although the precise ratio of spliced to unspliced RNA varies among strains (49). For an internal promoter, we used a fragment of the U3 region of the RSV LTR (50). This fragment includes promoter and enhancer sequences but excludes both the inverted repeat sequence at the 5' end, which is required for integration, and the polyadenylation signal at the 3' end.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In cells infected with the wild-type RSV, about half of the primary transcripts are spliced to generate env and v-src subgenomic mRNAs, although the precise ratio of spliced to unspliced RNA varies among strains (49). For an internal promoter, we used a fragment of the U3 region of the RSV LTR (50). This fragment includes promoter and enhancer sequences but excludes both the inverted repeat sequence at the 5' end, which is required for integration, and the polyadenylation signal at the 3' end.…”
Section: Resultsmentioning
confidence: 99%
“…The upstream gene was always fused in frame with the gag polyprotein and expressed from the LTR of the SRA-2 clone of RSV (50). The downstream gene was expressed in one of three ways: from a spliced subgenomic message, from an internal promoter, or from the EMCV IRES.…”
Section: Resultsmentioning
confidence: 99%
“…Structural and sequence analysis of the LTRs of several different retroviruses (Dhar et al, 1980;Ju & Skalka, 1980;Reddy et al, 1980;Sutcliffe et al, 1980;Van Beveren et al, 1980;Yamamoto et al, 1980;Donehower et al, 1981 ;Swanstrom et al, 1981) and the observation that proviruses generate short direct repeats of host DNA upon insertion Van Beveren et al, 1982;Hishinuma et al, 1981 ;Hughes et al, 1981 ;Majors & Varmus, 1981 ;Shoemaker et al, 1981) have revealed a remarkable resemblance between retroviruses and transposable elements (Calos & Miller, 1980). It has been proposed that the mechanism of integration of retroviruses may be similar to transposition and that retroviruses evolved from cellular movable genetic elements .…”
Section: Introductionmentioning
confidence: 99%
“…However, it is possible that both nonrecombining and recombining virions are capable of initiating and completing synthesis of two full genomic DNAs. Inefficient minus-strand DNA transfer, intermolecular minus-strand DNA template switching (3,34,39), degradation of viral DNA, formation of one and two long terminal repeat (LTR) circles (41,61,65), autointegration (46,62), and inefficient integration (19,20,29,63) could reduce the efficiency of provirus formation.…”
mentioning
confidence: 99%